Implementation of the Asmaul Husana Song as a Mnemonic Strategy in Early Childhood Islamic Education Learning - Evie Destiana; Eko Raharjo; Udi Utomo (Universitas Negeri Medan, 2026)
This study aims to explore the meaning, values, and lived experience of teachers and parents in using Asmaul Husna songs as a mnemonic strategy for memorizing the 99 Names of Allah at TK ABA I Candi Sidoarjo. Employing Moustakas's transcendental phenomenological approach, data were collected through in-depth semi-structured interviews, classroom observations, and document analysis with 7 participants (3 teachers, 4 parents). Analysis through epoché, horizonalization, clustering, and composite description yielded five major themes: (1) songs as carriers of living theological meaning; (2) psycho-musical effectiveness as a mnemonic tool; (3) embedded religious, social, and pedagogical values; (4) determinants of effective song quality; and (5) the dynamics of parental reinforcement at home. The findings propose a Psycho-Musical Mnemonic Framework for Islamic Early Childhood Education (PMMF-IECE) integrating song quality, teacher competence, children's psycho-musical engagement, and parental reinforcement as dynamically interacting components. This study enriches Islamic early childhood education literature with a phenomenological perspective that has been rarely examined.